Manajemen Budaya Religius di SD Plus Muhammadiyah Kota Sungai Penuh - Zunita, Irma; Imamora, Marjoni; Fazis, Muhammad (STKIP PGRI SITUBONDO, 2024)
The problem that is the background of this research is that Muhammadiyah Elementary School Plus Muhammadiyah City of Sungai Penuh is a school that has only recently become active again because previously it had not been operating because the number of students remained 2 people. In 2020, with the leadership of the new school principal, this school was able to develop and progress very rapidly, and is currently one of the favorite schools in Sungai Penuh City with 260 students. This is due to the advantages that exist in this school, namely religious activities and the inculcation of religious values applied by the school community so that it becomes a religious culture in this school. The purpose of this study was to find out how the management of religious culture at SD Plus Muhammadiyah Kota Sungai Penuh is in order to shape the religious character of students. This study used a qualitative approach with a case study type of research. The process of collecting data is done by means of observation, interviews and documentation. The technique of guaranteeing the validity of the data is by triangulating data sources and triangulating techniques. Data analysis techniques by doing data reduction, data presentation, and verification and draw conclusions. The findings show that: 1) Planning for a religious culture program starts with realizing the vision and mission and goals of the school, 2) Organizing, by forming persons in charge of implementing religious culture by forming daily picket teachers, and coordinators. 3) The implementation of religious culture at Muhammadiyah Elementary School Plus Muhammadiyah Kota Sungai Full. 4) Evaluation of the implementation of religious culture is carried out by means of direct observation or daily reports, with monthly evaluation meetings, and end of semester meetings.